Does body fat change with car ownership rates? A longitudinal survey of gender differences - Yuval Arbel; Chaim Fialkoff; Amichai Kerner (Journal of Urban Management, 2020)
Durable goods provide conventional proxies for household wealth, which, in turn, may increase the tendency to consume healthier food products and engage in leisure-time physical exercise. Higher car ownership levels, on the other hand, may reduce the tendency to participate in utilitarian, non-exercise-related physical activities such as walking to work and biking to do errands. Based on a recent longitudinal two-year Israeli Central Bureau of Statistics (CBS) survey, we examine the correlation between the number of cars owned by households and household members' body mass index (BMI) for adult female and male respondents below the workforce retirement age. Results indicate that projected BMI of native Israeli Jewish females and Jewish immigrants from Asian-African countries drops significantly, while compared with baseline native Jewish Israelis, the projected BMI decrease among Arab females is attenuated significantly with increased car ownership levels. These outcomes suggest that programs aimed at alleviating poverty may have the additional benefit of promoting obesity-reducing activities, particularly among the population of native Jewish Israeli females and immigrants from Asian African countries.
Keywords: H75; O18; I12; R41; 710; Body mass index; Car ownership; Durable goods; Obesity; Urban sprawl